Sociological investigation of the rule of law, transparency and accountability in relation to corruption in Punjab, Pakistan - Noor Khan; Dr. Tariq Mahmood Khan; Prof. Dr. Muhammad Iqbal Zafar* (Journal of Religion and Society, 2025)
Corruption is still a widespread worldwide problem that impacts every sphere of society and keeps getting bigger and more complicated. Because of its complexity, it is hard to pinpoint a single cause, which makes prevention and control efforts more challenging. Given its pervasive effects, scholars, decision-makers, and organizations from both the public and private sectors have underlined how crucial it is to research corruption in order to comprehend its fundamental dynamics and create workable solutions. Using structured survey data from 600 participants representing a range of groups, including government employees, professionals in the private sector, students, and members of civil society. This quantitative study investigates the sociological analysis of rule of law, transparency, and accountability in relation to corruption in Punjab, Pakistan. Interview schedules served as the main method of gathering data for the study, which was carried out in the Punjabi districts of Rawalpindi, Attock, Mianwali, and Faisalabad. Using both descriptive and inferential statistical techniques at the univariate and bivariate levels, the data were analysed using SPSS software. The results show that a combination of poor governance, lax law enforcement, a lack of transparency, economic hardships, and political favouritism trigger corruption in Pakistan. All of these elements work together to maintain and exacerbate corrupt practices in government agencies. The study also emphasizes the negative effects of corruption, such as the decline in foreign investment, the deterioration of public confidence in government agencies, the escalation of social inequality, and the slowed rate of economic growth. Numerous respondents expressed grave concerns about the deteriorating standard of public services as well as the growing rates of injustice and poverty that are linked to corruption. The study suggests extensive reforms aimed at bolstering legal frameworks, improving transparency, and encouraging increased civic engagement in light of these revelations. This study gives stakeholders and policymakers evidence-based recommendations for creating focused strategies that promote accountability, integrity, and good governance in Pakistan by identifying the main causes and effects of corruption. Keywords: Rule of law, accountability, transparency, meritocracy, and corruption.